Otimização combinatória para alocação de fontes renováveis em microrredes de corrente contínua - Fagundes, Minéia Cappellari [UNESP] (2014)
This study mainly presents a proposal for allocation of renewable energy sources in a microgrid for autonomous electric systems that uses direct current through a mathematical model written as a mixed integer quadratic problem ( PQIM ). The purpose of the mathematical model is to minimize the investment at the renewable energy installation and the costs related to electrical losses, attending the restrictions of system powers demands, the voltage drop limit, the current capacity of conductors, the maximum power generated by type of renewable energy allocated, the maximum capacity of the number of renewable energy sources to be allocated on each node of the system under study. To solve the problem two solution techniques were used. First, was used the Branch and Bound algorithm (B&B) with the implementation of the problem through the language of algebraic modeling (AMPL) and solved by the solver optimization CPLEX , subsequently the PQIM was solved through Chu-Beasley genetic algorithm implemented in Matrix Laboratory (MATLAB). For the B&B algorithm, was implemented a method for reducing the search space(EBCR) in order to reduce computational time . To validate the proposed mathematical model , was used a real test system with 20, 99 and 297 nodes, which is part of a project of public lighting of a popular residential subdivision in Ilha Solteira - SP , considering power in direct current